2016
DOI: 10.1002/cm.21336
|View full text |Cite
|
Sign up to set email alerts
|

The RNA‐binding protein LARP4 regulates cancer cell migration and invasion

Abstract: LARP4 is a La‐related RNA‐binding protein implicated in regulating mRNA translation, which interacts with poly(A)‐binding protein (PABP). We previously identified LARP4 in an RNAi screen as one of several genes that regulate the shape of PC3 prostate cancer cells. Here we show that LARP4 depletion induces cell elongation in PC3 cells and MDA‐MB‐231 breast cancer cells. LARP4 depletion increases cell migration and invasion, as well as inducing invasive cell protrusions in 3D Matrigel. Conversely, LARP4 over‐exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
47
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 33 publications
7
47
1
Order By: Relevance
“…11 Another experiment illuminates that LARP4 inhibits prostate cancer cell migration and invasion. 24 As for the prognostic value of circ-LARP4, a previous cohort study reports that circ-LARP4 expression is decreased in tumor tissue than that in paired adjacent tissue, and is negatively correlated with Federation of Gynecology and Obstetrics stages and survival in ovarian cancer patients, which is partially in line with our results. 25 In this study, we found that circ-LARP4 was upregulated in non-tumor tissue compared with tumor tissue, and tumor tissue circ-LARP4 high expression was associated with decreased Enneking stage, elevated good response rate, and more satisfactory survival profiles in osteosarcoma patients.…”
Section: Effect Of Circ-larp4 and Mir-424 On Chemosensitivity In Sasupporting
confidence: 90%
See 2 more Smart Citations
“…11 Another experiment illuminates that LARP4 inhibits prostate cancer cell migration and invasion. 24 As for the prognostic value of circ-LARP4, a previous cohort study reports that circ-LARP4 expression is decreased in tumor tissue than that in paired adjacent tissue, and is negatively correlated with Federation of Gynecology and Obstetrics stages and survival in ovarian cancer patients, which is partially in line with our results. 25 In this study, we found that circ-LARP4 was upregulated in non-tumor tissue compared with tumor tissue, and tumor tissue circ-LARP4 high expression was associated with decreased Enneking stage, elevated good response rate, and more satisfactory survival profiles in osteosarcoma patients.…”
Section: Effect Of Circ-larp4 and Mir-424 On Chemosensitivity In Sasupporting
confidence: 90%
“…And the LARP4 gene, the location of circ‐LARP4, has also been found to be a tumor suppressor, for example, a recent experiment elucidates that LARP4 gene represses cell motility and migration in ovarian cells . Another experiment illuminates that LARP4 inhibits prostate cancer cell migration and invasion . As for the prognostic value of circ‐LARP4, a previous cohort study reports that circ‐LARP4 expression is decreased in tumor tissue than that in paired adjacent tissue, and is negatively correlated with Federation of Gynecology and Obstetrics stages and survival in ovarian cancer patients, which is partially in line with our results .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, we found that stomach adenocarcinoma (STAD) tends to have disproportionately higher number of NMD-elicit mutations and a mutator phenotype that selects for NMD-elicit mutations in LARP4B, EIF5B and PTEN . Although the potential relationship between LARP4B or EIF5B and cancer has been previously reported31323334, the link between these genes and hypermutation was previously unrecognized. It is conceivable that NMD-mediated hypofunction of LARP4B or EIF5B permits the hypermutated cancer cells to cope with a high mutation load by delaying translation.…”
Section: Discussionmentioning
confidence: 99%
“…Some members of this superfamily, such as LARP1 [169][170][171][172] and LARP6 [173], control the expression of target transcripts and promote the progression of several cancer types. On the other hand, LARP4A [174] and LARP4B [175] are tumor-suppressive RBPs, which inhibit cancer metastasis and growth, respectively.…”
Section: Rna-binding Proteins (Rbps) the Silent Guardians Of The Tramentioning
confidence: 99%